The Development of Rhythmic Criticism of Ibn Rasheq Al-Qayrawani in his Book Al-Umda - Hussein Aliwi , Asst.Prof Alaa (Journal of College of Education, 2022)
Rhythmic criticism represents one of the basic premises in dealing with poetic text, especially in ancient Arabic criticism. This was clearly embodied in the book Al-Umda by Ibn Rashiq Al-Qayrawani (456 AH), which collected a large number of rhythmic issues and dealt with them with explanation, analysis and application, and then employed them in the service of poetry criticism. Among the most important things Al-Qayrawani emphasized is the connection between meter and rhyme, temperament and taste in the science of prosody, rhythm and chanting, the relationship of erratic terms to meaning and al-Qawadisi poetry.